2021
DOI: 10.1016/j.compbiomed.2021.104631
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential plant bioactive as SARS-CoV-2 Spike protein and human ACE2 fusion inhibitors

Abstract: The Spike receptor binding domain (S-RBD) from SARS-CoV-2, a crucial protein for the entrance of the virus into target cells is known to cause infection by binding to a cell surface protein. Hence, reckoning therapeutics for the S-RBD of SARS-CoV-2 may address a significant way to target viral entry into the host cells. Herein, through in-silico approaches (Molecular docking, molecular dynamics (MD) simulations, and end-state thermodynamics), we aimed to screen natural molecules from dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 75 publications
0
58
0
Order By: Relevance
“…For instance, Abbas et al, used computational approaches to study the impact of different mutations on the binding and infectivity [ 18 , 20 , 39 , 40 ]. Moreover, using these approaches many small molecules drugs are tested against different proteins of SARS-CoV-2 [ [41] , [42] , [43] , [44] , [45] , [46] ]. Therefore, herein we used computational approaches to study the reported 250 genomes of SARS-CoV-2 isolated from Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Abbas et al, used computational approaches to study the impact of different mutations on the binding and infectivity [ 18 , 20 , 39 , 40 ]. Moreover, using these approaches many small molecules drugs are tested against different proteins of SARS-CoV-2 [ [41] , [42] , [43] , [44] , [45] , [46] ]. Therefore, herein we used computational approaches to study the reported 250 genomes of SARS-CoV-2 isolated from Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…We investigated the antiviral activity of the isolated compound against SARS-CoV-2 together with other compounds isolated in our previous study [ 15 ] including four naphthopyrones, namely, flavasperone ( 1 ), rubrofusarin B ( 2 ), aurasperone A ( 3 ), fonsecinone A ( 4 ) and aspernigrin A alkaloid ( 5 ). Several in silico techniques, including molecular docking, molecular dynamics simulations (MDS), and end-state thermodynamics, are widely used as valuable tools for explaining the biological activities and the binding ability of the tested molecules to important therapeutic targets [ 16 , 17 , 18 ]. SARS-CoV-2 has two proteases, the main protease (M pro ), and the papain-like protease (PL pro ), which are essential for processing the viral non-functional proteins, and they are among the most important therapeutic targets used for the treatment of COVID-19 [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Then, researchers reported that some feline coronavirus drugs are strong candidates for the treatment of patients with SARS-CoV-2 ( Vuong et al, 2020 , Paltrinieri et al, 2021 ). Presently, an increasing number of SARS-CoV-2 drugs have been found or identified by in silico work on natural molecules against SARS-CoV-2, thereby potentially supplying new candidate drugs for treating cats with FCoV in the future ( Bhardwaj et al, 2021a , Bhardwaj et al, 2021c , Bhardwaj et al, 2021b , Sharma et al, 2021 , Singh et al, 2021a , Singh et al, 2021b , Singh et al, 2021c ; Singh et al, 2021d). Based on the above information, the characteristics of FCoV and its infection among cats might shed light on the understanding of human infection with SARS-CoV-2 and vice versa.…”
Section: Introductionmentioning
confidence: 99%